The Effect of Artificial Tear Treatment on Central Corneal Thickness in Dry Eyes - Khan, Umair Naeem; Humayun, Fakhar; Naeem, Saquib; Butt, Waqas Rahim; Khan, Taimoor Ashraf; Qadir, Abdul (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the role of artificial tear treatment on central corneal thickness in patients with dry eyes coming to a tertiary care eye hospital.Study Design: Quasi-experimental study.Place and Duration of Study: Tertiary Care Eye Center, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from May to Nov 2022.Methodology: The study included central corneal thickness of 210 eyes (n=210) of 110 patients with dry eye disease measured before and after treatment with continuous use of artificial tear drops one month apart, patients were diagnosed on the presence of symptoms such as burning, dryness, pain, irritation, grittiness followed by slit lamp examination for marginal tear meniscus(